On fuzzy points in semigroups - Kyung Ho Kim (International Journal of Mathematics and Mathematical Sciences)
We consider the semigroup S¯ of the fuzzy points of a semigroup S, and discuss the relation between the fuzzy interior ideals and the subsets of S¯ in an (intra-regular) semigroup S.